Deletion of TNF‐like weak inducer of apoptosis (TWEAK) protects mice from adipose and systemic impacts of severe obesity. (8th March 2014) - Bennett, Grace; Strissel, Katherine J.; DeFuria, Jason; Wang, Junpeng; Wu, Dayong; Burkly, Linda C.; Obin, Martin S.
<x xml:space="preserve">Abstract</x> Objective To investigate the role of TNF‐like weak inducer of apoptosis (TWEAK) in pathological adipose tissue (AT) remodeling and complications of obesity. Methods Wild type (WT) and TWEAK knockout (KO) mice were fed normal diet (ND) or a high fat diet (HFD) for up to 17 weeks. Adipocyte death was induced using an established transgenic mouse model of inducible adipocyte apoptosis (FAT‐ATTAC). Metabolic, biochemical, histologic, and flow cytometric analyses were performed. Results TWEAK and its receptor, fibroblast growth factor‐inducible molecule 14 (Fn14) were upregulated in gonadal (g)AT of WT mice after HFD week 4 and 24 h after induction of adipocyte apoptosis. Phenotypes of KO and WT mouse were indistinguishable through HFD week 8. However, at week 17 obese KO mice had ∼30% larger gAT adipocytes and gAT mass than WT mice, coincident with reduced adipocyte death, enhanced insulin signaling, Th2/M2 immune skewing, fewer thick collagen fibers, and altered expression of extracellular matrix constituents and modulators that is consistent with reduced fibrosis and larger adipocytes. KO mice were less steatotic and became more insulin sensitive and glucose tolerant than WT mice after HFD week 12. Conclusion TWEAK constrains "healthy" gAT expansion and promotes metabolic complications in severe obesity.